Perancangan Web Jasa Penyewaan Sound System Pada Eman Sounds - Andriansah; Ika Yuniva; M. Seprian Alfath Arkab (Jurnal Jaring SainTek, 2020)
Eman Sounds is a business venture in the field of sound system rental services. The Eman sounds does not currently have a website application. The leasing service transaction system is still done conventionally, where if anyone wants to rent a sound system for a wedding or other official event can come directly to the Eman Sounds to see and rent it. For transaction reports sound system rental services are still recorded with paper so as to allow for data loss and errors in recording transactions. The purpose of this study is that the author will design a web sound system rental service for Eman Sounds so that it is expected to simplify the process of leasing transactions and making rental reports. The author uses the system development method, namely the waterfall model for this study. The use of PHP and HTML programming languages ​​the author uses to create web rental services and MYSQL as the database. The results of this study are expected that with a web design sound system rental service can help Eman Sounds in the process of managing rental transactions and reports.